Development of Computer Program to Analyse Combustion Products Resulting from Incineration of Solid Fuels - Mohamed, Harimi (2000)
Numerous technologies have been developed to combust solid fuels and waste in a commercially useful manner. Impetus for technology development includes optimizing energy recovery, capitalizing upon economies of scale, maximizing the potential applications of solid fuels, and achieving compliance with present and expected environmental regulations. The goal of this research is to develop a computer program for analysing the chemical products from incineration of solid fuel. The objective is to compute the concentrations of 12 chemical products at a given temperature and excess air, with total flue gas pressure equals to 1 atm. Those concentrations can be used as thermodynamic indicators, for lowering the emissions by adequately organizing and conducting the combustion process. The computer program also takes into account the possibility of further extension. The products of combustion concerned include; carbon dioxide C02, carbon monoxide CO, water vapor H20, hydrogen H2, sulfur dioxide S02, sulfur trioxide S03, nitric oxide N O, nitrogen dioxide N02, hydrogen chloride HC I, chlorine Ch, oxygen O2, and nitrogen N2. Chemical combustion and equilibrium analysis form the main part of this research. For the first analysis 6 equations are deduced from mole balance, and 6 other equations are deduced from the second analysis by using the chemical equilibrium constants. The 12 equations are non-linear, and therefore numerical method is used i.e. the Newton iteration method for its rapid con vergence. The output from this computer program are compared with the result of research carried out by the Institute of Nuclear Sciences (INS), which is based on the application of the developed model for computing the chemical thermodynamic equilibrium of a system formed by compounds and elements contained in the Kolubare [Yogoslavia] basin lignite. Combustion simulation was done for eight lignite compositions with temperatures from 800 to 1700 K, pressure 1 atm, and 25% excess air. The results obtained from the combustion of such a solid fuel show that there is no significant difference between the two sources [INS & Program] as proved by using statistical T -test whatever difference in the results that are noticed, vary from one compound to another. This is due to different models used in computing the chemical equilibrium constants and the number of products used. The results given by INS are related to more than 12 unknowns in comparison to the developed computer program. It is recommended to add to the developed computer program the equation of energy, from which the adiabatic temperature can be computed. For the accuracy of the computer program, other compounds may be added such as H, OH, H02, N20, HN02, H202, SO, N, 0, and CH4. Beside this the humidity in the air should be taken into account. Additional subroutine may be inserted in the computer program, for computing some thermodynamic parameters and also amount of additional fuel in case where the solid waste have unsufficient heating value. Options for designing furnace and the auxiliary equipments of an incinerator can also be included.